Efektivitas Model Pembelajaran Blended Learning Terhadap Motivasi dan Kemampuan Pemecahan Masalah pada Materi Peluang - Nafisatul Mu'awanah Nafisatul Muawanah; Dita Yuzianah; Puji Nugraheni (Universitas Muhammadiyah Purworejo, 2022)
The objectives of this study are: (1) to find out whether the motivation of students who use the Blended Learning model is better than the motivation of students who use conventional learning models and (2) To determine whether students' problem-solving abilities of those who use the Blended Learning model are better than the problem-solving abilities of students who use the conventional learning model. This research method uses quantitative research with the type of experimental research. The population in this study was all class IX SMP Negeri 33 Purworejo school year 2021/2022 totaling 214 students. The sampling technique used random cluster sampling so that class IX D was chosen as the experimental class and class IX F as the control class. The results of the hypothesis test of the difference in the mean of the two groups were obtained, and H0 was accepted. This means that the motivation and problem-solving ability in the experimental class is the same as the motivation and problem-solving ability in the control class. Therefore, it can be concluded that (1) the learning motivation of students who use the Blended Learning learning model is not better than the learning motivation of students who use the conventional learning model (2) the problem-solving ability of students who use the Blended Learning learning model is not better than the motivation and ability of students who use the Blended Learning model student problem solving using conventional learning models.